Determinación del coeficiente de cultivo kc para maní arachis hypogaea l bajo invernadero en la granja Santa Ines - Campoverde Anguisaca, Israel Gustavo (2017)
The manual is an annual crop that requires a technified irrigation system and takes into account the edaphoclimatic conditions of the sector, where rainfall does not always meet the water requirements of crops; Agriculture is the activity that has the highest water demand in the world, starting from the irrigation that is the activity that consumes 70% of this resource; So that food production and water use are inseparably related and compensate for water loss through evapotranspiration (ET) and to compensate for the deficiencies of rainfall, it is necessary to use the resource efficiently, correctly calculating the Irrigation sheets With the use of both climate and crop information, evapotranspiration (ET) is the sum of the evaporation of the soil surface known as a physical phenomenon by which water passes the liquid a vapor and the process of transpiration is It is based on the vaporization of water contained in plant tissues which is transferred to the atmosphere, and the factors that directly and indirectly affect evaporation and transpiration are: climate, crop characteristics, soil and irrigation water , Starting from this coefficient of cultivation (KC). It is one of the main parameters to know the water requirements of the plant, so it is of great importance to carry out more studies incorporating this parameter to the different local areas to consider the edaphoclimatic and (KC), for the cultivation of peanuts (Arachis hypogaea L.) by the indicator method to generate the KC curve. During its phenological stage, Under controlled conditions In greenhouse. In the present study, weekly values of the crop coefficient (KC) were determined using the field weights, after the values obtained were separated for each phenological phase, the water requirements were also determined for each phenological stage of the crop By means of the Formulas proposed from the determined coefficients. Sampling development targeted 10 random apple crop plants at which weight was recorded before and after irrigation, starting with a total of 40 experimental units for the determination of crop evapotranspiration (ETC) and for obtaining The reference evapotranspiration (ETO), which consists of a hypothetical crop such as grass, which consists of the same process taking 5 plants of the reference culture randomly taken from a total of 10 units. The results obtained for each physiological phase in the KC determination were for the initial phase 0.46; For the development phase 1.06; Mid-stage 1.12 and the final stage 0.54. The vegetative period is influenced by the variety, the albedo, the climate and the management of the same, in which we obtained for each phase (initial, development, mid-development and final) 25/30/35/20 days respectively. The highest water requirement has been presented in the development phase of a project with 2.2 liters / plant, the decommissioning in the final phase is a rainfed crop, it is recommended to carry out the test on other edaphic climatic periods, for the determination of the crop coefficient In Peanut during the different stages of the year and the density of sowing.